2003
DOI: 10.1001/archinte.163.18.2187
|View full text |Cite
|
Sign up to set email alerts
|

CD4 T-Lymphocyte Recovery in Individuals With Advanced HIV-1 Infection Receiving Potent Antiretroviral Therapy for 4 Years<subtitle>The Swiss HIV Cohort Study</subtitle>

Abstract: At 4 years, only 39% of individuals treated with HAART reached a CD4 T-lymphocyte count of 500/microL or greater, and 16% with CD4 T-lymphocyte counts less than 200/microL remained susceptible to opportunistic infections. Treatment interruptions, a poor virologic response, and older age were the major factors negatively affecting the recovery of CD4 T lymphocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

45
264
3
12

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(324 citation statements)
references
References 33 publications
45
264
3
12
Order By: Relevance
“…12,13 Previous studies have found that impaired IL-7 responsiveness is significantly associated with poor CD4 T-cell recovery following cART. 14,15 Various clinical factors have been associated with impaired CD4 T-cell reconstitution following cART, including lower CD4 T-cell counts at initiation of cART, [16][17][18][19] being older at cART initiation 1,17,19,20 and higher levels of immune activation both before and while on cART as measured by T-cell activation markers (such as human leukocyte antigen (HLA)-DR þ CD38 þ expression). [21][22][23][24] Multiple host genetic factors have also been found to influence CD4 T-cell recovery.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Previous studies have found that impaired IL-7 responsiveness is significantly associated with poor CD4 T-cell recovery following cART. 14,15 Various clinical factors have been associated with impaired CD4 T-cell reconstitution following cART, including lower CD4 T-cell counts at initiation of cART, [16][17][18][19] being older at cART initiation 1,17,19,20 and higher levels of immune activation both before and while on cART as measured by T-cell activation markers (such as human leukocyte antigen (HLA)-DR þ CD38 þ expression). [21][22][23][24] Multiple host genetic factors have also been found to influence CD4 T-cell recovery.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, some studies with longer follow-up periods have established that slight increases continue for about 2 years, reaching a plateau thereafter [2,4,21,22]. Other studies that also reported the response of CD4 count to HAART found increases of 180-201 cells/mL at 48 weeks in patients treated with diverse antiretroviral regimens [23], 200 cells/mL in naïve patients at 48 weeks [24], 126-187 cells/mL at 48 weeks in patients at various disease stages [5], 143 cells/mL at 72 weeks in patients starting indinavir-containing regimens [22], 186-280 cells/mL in naïve patients at 96 weeks depending on different baseline strata of CD4 [4], 190-423 cells/mL at 48 months in patients on continuous and discontinuous HAART [10], and 299 cells/mL at 48 months in naïve and experienced patients, with higher final absolute values for the less advanced clinical stages [2].…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of viral load as a result of HAART has been found to be in the range 37-91% depending on various factors such as prior experience with HAART, initial CD4 cell count and viral load, length of the follow-up period, type of analysis and threshold used for undetectability [3][4][5][6][7]10,23,24,[30][31][32][33][34][35]. Although some authors did not find differences in viral responses depending on history of prior antiretroviral treatment [30], most studies [7,25,35] confirm our finding of greater virological responses to HAART in naïve than in experienced patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, antiretroviral (ARV) therapy is potent, convenient/simple or easy and usually well tolerated, and causes capable of reducing HIV blood concentration to undetectable values within a few weeks from therapy initiation and of inducing a robust and sustained CD4 T-cell gain. 1,2 The introduction of HIV protease inhibitors (PIs) in 1995 and the application of highly active anti-retroviral therapy (HAART), i.e. combination of PI with other antiretrovirals, mainly inhibitors of the HIV reverse transcriptase, increased the life expectancy of of HIV-positive patients .…”
Section: Introductionmentioning
confidence: 99%